TRADISI MUJAHADAH PEMBACAAN DZIKIR RATIB AL-‘ATTAS DI PONDOK PESANTREN RAUDLATUL BANAT CIREBON: STUDI LIVING QUR’AN - Nurkholidah Nurkholidah; Achmad Lutfi; Wati Herningsih (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2021)
Raudlatul Banat Islamic Boarding School has routine activities in the form of recitation of dzikir RÄtib Al-â€˜Aá¹á¹Äs, which contains three elements, namely selected verses of the Qurâ€™an, prayer of the prophet, and prayer of choice. This study uses descriptive qualitative methods with the type of research Field Research and Library Research. The result of the research in this paper can reveal that the mujahadah tradition of reciting dzikir RÄtib Al-â€˜Aá¹á¹Äs is a socio-religious practice that developed in Raudlatul Banat Islamic Boarding School. The activity is carried out routinely every Wednesday night, which is the routine of Abah Hud bin Yahya during his lifetime with senior clerics and Kyais in the hall of Raudlatul Banat Islamic Boarding School. After Abah Hud died, the routine was continued by his son, namely H. Syarif Ahmad Tholib Yahya. Meanwhile, the routines of the santri were held on the Sunday night of the evening at the Raudlatul Banat Islamic Boarding School. The significance of the mujahadah tradition is the reading of the remembrance of RÄtib Al-â€˜Aá¹á¹Äs at Raudlatul Banat Islamic Boarding School based on the sociology theory of Karl Mannheim knowledge there are three categories of meaning obtained, namely the objective meaning as the family routines of Abah Syarif Hud bin Yahya and santri, Expressive meaning as practice that draws closer to God and the form of obedience to the teacher, as well as the meaning of the documentary as a whole culture. Then some of the transformations felt by the perpetrators include a calmer heart, facilitated all his affairs by Allah SWT, launched his sustenance, granted all his desirer, and protected from all vices..Â